Resolución por inejecución de obligaciones mediante intimación del acreedor: algunos comentarios sobre su regulación civil y registral - Ortega Piana, Marco Antonio (2020)
In the event of a serious breach of obligations, it’s logical the representation that assists the creditor exclusively affected, the possibility of resolve the agreement, for loss of interest in claiming the due; however, to achieve this purpose, the law has the necessary observance of certain requirements, which cannot be ignored within the framework of private autonomy, or because the creditor wants to resolve the agreement unilaterally. It’s precisely the affectation of the indicated interest that makes it possible to distinguish between immediate and deferred resolution procedures, proposing that the so-called intimidation resolution be considered in the last group, given that it’s assumed that the creditor maintains interest in to obtain the due, although it will lose it if, within the granted period, the unfaithful party maintains the state of non-performance of obligations. Being a full-fledged resolution, in which a constitutive jurisdictional qualification is omitted, it should be able to register said resolution, despite the fact that the current registry regulation does not expressly authorize it, for which purpose, warning of contingencies, certain alternatives are proposed for reasonably protect the interests of the parties involved.